PENGARUH KARAKTERISTIK DEMOGRAFIS (USIA, GENDER,PENDIDIKAN), MASA KERJA DAN KEPUASAN GAJI TERHADAP KOMITMEN AFEKTIF) (Studi Pada Tenaga Paramedik Non-PNS RSUD Kota Semarang) - Simson Hutagalung; Mirwan Surya Perdhana (Faculty of Economics and Business Diponegoro University, 2016)
The purpose of this research is to extend previous research on employee commitment to theirorganization within with the measurability and the fitness of the tested and reliable employeecommitment scale items in a non-western culture within focus to investigate the effect ofdemographic characteristic (age, gender, education), tenure and pay satisfaction on affectivecommitment based background of the phenomena that occur in the commitment of contractparamedical employees at the General Hospital of Semarang.This research was conducted at the General Hospital of the city with A quantitativeapproachment.The data collection using five-point Likert scaled questionnaire administered to 75contract paramedical employees at the General Hospital of Semarang.The results indicates that there are no significant effect between both demographic characteristic(age, gender, education) and tenure on affective commitment.Conversely, the result indicate thereis a positive significant correlation between pay satisfaction towards affective commitment at theGeneral Hospital of Semarang.Keywords: Demographic characteristic (age, gender, education, tenure and affective commitment)